Addressing the global Challenge of NCDs using a Risk Factor approach: voices from around the world. Issue 4 (16th February 2021) - Saran, Rajiv; Randolph, Elizabeth; Omollo, Kathleen Ludewig
Abstract: Noncommunicable diseases (NCDs) are growing at an alarming rate around the world, drawing attention in multiple United Nations high‐level meetings, the Sustainable Development Goals, regional alliances for NCDs, and in scientific research agendas. In 2018, the World NCD Federation selected the University of Michigan from seven universities around the world to host the 2nd World NCD Congress in 2020. For the scientific program, we defined an intersecting matrix of "risk factors" and "disease‐oriented" lenses for examining NCDs to highlight the multiple risk factors that contribute to major NCDs. Through deliberation with two committees representing over 50 individuals and 11 countries, eight risk factors were selected for the scientific program: social determinants of health and demographics, climate and environment, stress, sleep, substance use, nutrition, and physical activity, and genetics. These eight risk factors served as submission categories for a call for abstracts as well as topics for the planned plenary sessions. In April 2020, we pivoted our approach when meeting in person for a conference was no longer feasible. Building upon the risk factor model, we shifted the invited talks to invited articles for publication as a special collection for FASEB BioAdvances. We are delighted to launch this collection with 13 invited articles by 32 experts from ten countries. Significant transferable lessons about key risk factors and prevention of NCDs from this collection could be leveraged in various geographic areas and in settings with varying levels of resources, as they cover a diverse range of topics from community‐level interventions to indigenous leadership structures to national policies to intergovernmental programs.